Field cancerization in stomatognathic system - Vidya Kadashetti; K M Shivakumar; Rajendra Baad; Nupura Vibhute; Uzma Belgaumi; G Sushma; Snehal Patil (Wolters Kluwer Medknow Publications, 2016)
Worldwide, head and neck squamous cell carcinoma is the sixth most common malignancy in men. The parts of Southeast Asia, head and neck squamous cell carcinoma is the most common malignancy, accounting for up to 50% of malignant tumors. Oral squamous cell carcinoma is believed to arise from a series of genetic changes induced by carcinogens, ultimately leading to clinical and microscopic changes summating to form an invasive neoplasm. The principal etiological factors such as tobacco and alcohol are responsible for DNA mutation activating oncogenes interfering with tumor suppressor genes and interacting with various epithelial growth factors. Slaughter in 1953 proposed the concept of field cancerization. He hypothesized that an area of epithelium is preconditioned by a carcinogenic agent. Such a carcinogenic influence if operative long enough in time and intense enough in exposure produce an irreversible change in cells and cell groups in a given area and so that the process toward cancer becomes inevitable. Thus, oral squamous cell carcinoma is multicentric in origin, through a process of field cancerization would seem to be an important factor in the persistence or recurrence of oral squamous cell carcinoma. As local and systemic therapies for primary tumor do not appear to prevent multifocally, the prognostic implications of field cancerization change may be substantial. The occurrence of second primary tumors may not be the major cause of mortality in the head and neck cancer patients but has a high impact on mortality and the treatment program of these patients. Careful screening procedures, carried out to detect multifocal tumors at an early stage, should improve survival in these patients.